Wound dressing based on chitosan/hyaluronan/nonwoven fabrics: Preparation, characterization and medical applications - Abdel-Rahman, Rasha M; Abdel-Mohsen, A M; Hrdina, R; Burgert, L; Fohlerova, Z; Pavliňák, D; Sayed, O N; Jancar, J (International journal of biological macromolecules, 2016)
Thin layers of chitosan (positively charged)/sodium hyaluronate (negatively charged)/nonwoven fabrics were constructed by polyelectrolyte multilayer pad-dry-cure technique. Pure chitosan (CS) was isolated from shrimp shell and immobilized onto nonwoven fabrics (NWFs) using citric acid (CTA) as cross linker and solvent agents through a pad-dry-cure method. The prepared thin layer of chitosan citrate/nonwoven fabrics (CSCTA/NWFs) were consequently impregnated with hyaluronan (CSCTA/HA/NWFs) in the second path through a pad-dry-cure method. Chitosan/hyaluronan/nonwoven fabrics wound dressing was characterized by different techniques such as FTIR-ATR, TGA and SEM. The antibacterial activity and the cytotoxicity of the dressing sheets were evaluated against Escherichia coli (E. coli) and Streptococcus aureus (S. aureus), mouse fibroblast (NIH-3T3) and keratinocytes (HaCaT) cell lines, respectively. The cell-fabrics interaction was also investigated using fluorescence microscope, based on live/dead staining assay of 3T3 cells. The healing properties of the new wound dressing were evaluated and compared with the control sample.
Keywords: hojení ran; Staphylococcus aureus; obvazy; Chitosan; Humans; Cytotoxicity; Bandages; Escherichia coli; lidé; textilie; antibakteriální látky; zvířata; myši; buňky NIH 3T3; Hyaluronan; Wound Healing; Mice; NIH 3T3 Cells; Nonwoven fabrics; Anti-Bacterial Agents; Textiles; kyselina hyaluronová; Healing properties; Animals; Hyaluronic Acid; chitosan